COASTAL CHARACTERISTICS OF SOUTH SINGKEP AREA, RIAU ISLANDS PROVINCE - Noor C.D. Aryanto; Setyanto C.D. Pranoto (Marine Geological Institute of Indonesia, 2014)
Observations of coastal characteristics, such as coastal constituent lithology, oceanographic processes and the influence of human activities along the coastal area, are the factors that affect the coastal typology. The typology of coastal area can be divided into 3 types namely: (1) Sandy beaches, dominated by medium size quartz sand, gravelly sand and silt of alluvium deposits ; (2) Rocky beaches that belong to the Tanjung Buku Granite lithologic units and Persing metamorphic complex, its beach slope between 5° and 15°, and a fault structure encountered. The steep beach slopes (45°-50°) trends to offshore with the maximum depth of 28 meters below the sea level at the distance of 3.5 km from the its shore line. At the depth of 20 m, there are a foot slope of 1.5 km width interpreted as the fault plane; (3) Muddy beaches is characterized by mangroves, gentle beach slopes until flats. Those sandy and muddy beaches are alluvial deposits of Quarternary sediments. Keywords: Coastal characteristics, relief, oceanographic processes and South Singkep Pengamatan karakteristik pantai, seperti litologi penyusun tubuh pantai, proses-proses oseanografi serta pengaruh aktivitas manusia di sepanjang pantai merupakan faktor-faktor yang mempengaruhi tipologi pantai. Tipe pantai di daerah penelitian, dapat dibagi menjadi 3 jenis pantai, yaitu: (1) Pantai berpasir, disusun oleh dominasi pasir kuarsa, berukuran menengah, pasir kerikilan dan lanau dari alluvium, serta kemiringan pantai rendah; (2) Pantai berbatu merupakan bagian dari satuan batuan Granit Tanjung Buku dan Kompleks metamorfik Persing, kemiringan pantai antara 5° hingga 15° serta dijumpai sesar. Kearah laut kemiringan lerengnya makin besar (45°-50°) dengan bagian terdalam mencapai 28 meter pada jarak 3,5 km dari garis pantai. Pada kedalaman laut 20 m, terdapat kaki lereng ( foot of slope) dengan lebar 1,5 km yang diperkirakan sebagai bidang sesar; (3) Pantai berlumpur yang dicirikan oleh tanaman bakau memiliki kemiringan pantai yang relatif datar.Pantai berpasir dan pantai berlumpur merupakan endapan aluvium yang berumur Kuarter. Kata kunci: Karakteristik pantai, relief, proses oseanografi dan Singkep Selatan